Effect of web-based health education on nursing students' knowledge, adaptive healthy measures and attitudes regarding polycystic ovary syndrome: a randomized controlled trial - Rasha A. Mohamed; Nagwa N. Taref; Nehmedo E. Osman; Nawal Hamdy Ahmed Keshta; Mahmoud A. Alboghdady; Marzouk M. Marzouk; Abeer A. Almowafy; Eman A. Fadel (BMC, 2024)
Abstract Background Polycystic ovary syndrome (PCOS) is a complex endocrine disorder affecting women of reproductive age, and it has emerged as a significant global public health issue. This study aimed to investigate the effects of web-based health education on nursing students' knowledge, adaptive healthy measures, and attitudes toward PCOS. Methods A two-group randomized controlled trial (RCT) with pre-test and immediate post-test assessments was conducted. Study participants were recruited using a simple random sampling method from the Faculty of Nursing, Mansoura University, Egypt. A questionnaire consisting of six sections was developed to collect data, which was analyzed with the SPSS 23.0 using Student's t-test, Pearson's correlation test, and chi-square test analysis of variance. Results The analysis revealed a significant increase in knowledge scores post-intervention, with the web-based learning groups (32.2 ± 10.5) outperforming the traditional learning group (22.1 ± 10.2), with (p < 0.05). Similarly, there was a notable improvement in adaptive healthy measures scores post-intervention, with the web-based learning group (8.9 ± 2.4) showing better results than the traditional group (6.5 ± 2.9), with (p < 0.05). In terms of attitudes toward PCOS, the web-based group (18.2 ± 4.9) displayed a significant improvement compared to the traditional group (11.7 ± 5.2), with (p < 0.05). Conclusions The findings suggest that web-based learning is more effective than traditional methods in enhancing nursing students' knowledge, adaptive healthy measures, and attitudes toward PCOS. Trial Registration : This study was registered by Clinical Trials.gov Identifier: (NCT06192381|| https://www.clinicaltrials.gov/ ) on 5-1-2024.